Allele-specific RNA interference rescues the long-QT syndrome phenotype in human-induced pluripotency stem cell cardiomyocytes - Matsa, Elena; Dixon, James E.; Medway, Christopher; Georgiou, Orestis; Patel, Minal J.; Morgan, Kevin; Kemp, Paul J.; Staniforth, Andrew; Mellor, Ian; Denning, Chris (Oxford University Press, 2013)
Aims Long-QT syndromes (LQTS) are mostly autosomal-dominant congenital disorders associated with a 1:1000 mutation frequency, cardiac arrest, and sudden death. We sought to use cardiomyocytes derived from human-induced pluripotency stem cells (hiPSCs) as an in vitro model to develop and evaluate gene-based therapeutics for the treatment of LQTS. Methods and results We produced LQTS-type 2 (LQT2) hiPSC cardiomyocytes carrying a KCNH2 c.G1681A mutation in a IKr ion-channel pore, which caused impaired glycosylation and channel transport to cell surface. Allele-specific RNA interference (RNAi) directed towards the mutated KCNH2 mRNA caused knockdown, while leaving the wild-type mRNA unaffected. Electrophysiological analysis of patient-derived LQT2 hiPSC cardiomyocytes treated with mutation-specific siRNAs showed normalized action potential durations (APDs) and K+ currents with the concurrent rescue of spontaneous and drug-induced arrhythmias (presented as early-afterdepolarizations). Conclusions These findings provide in vitro evidence that allele-specific RNAi can rescue diseased phenotype in LQTS cardiomyocytes. This is a potentially novel route for the treatment of many autosomal-dominant-negative disorders, including those of the heart.